Africaphes gen. nov., a new genus of Stenichnini in Burundi and Rwanda (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2025)
Africaphes gen. nov. is described to accommodate A. quadripunctatus sp. nov. (Burundi; type species of the genus) and A. bipunctatus sp. nov. (Rwanda). The new genus belongs to a Microscydmus-like group of genera with trimerous antennal clubs, posteriorly closed procoxal cavities, a carinate mesoventral process and the metaventral intermetacoxal process composed of a pair of long katepisternal spines, but differs, among other characters, in the submental region delimited by deep lateral submental sulci. An updated key to world genera of Stenichnini, and, to facilitate identification, a separate key to continental Afrotropical genera are given.